Robotic Cardiac Surgery in Europe: Status 2020 - Cerny, Stepan; Oosterlinck, Wouter; Onan, Burak; Singh, Sandeep; Segers, Patrique; Bolcal, Cengiz; Alhan, Cem; Navarra, Emiliano; Pettinari, Matteo; Van Praet, Frank; De Praetere, Herbert; Vojacek, Jan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: European surgeons were the first worldwide to use robotic techniques in cardiac surgery and major steps in procedure development were taken in Europe. After a hype in the early 2000s case numbers decreased but due to technological improvements renewed interest can be noted. We assessed the current activities and outcomes in robotically assisted cardiac surgery on the European continent. Methods: Data were collected in an international anonymized registry of 26 European centers with a robotic cardiac surgery program. Results: During a 4-year period (2016-2019), 2,563 procedures were carried out [30.0% female, 58.5 (15.4) years old, EuroSCORE II 1.56 (1.74)], including robotically assisted coronary bypass grafting (n=1266, 49.4%), robotic mitral or tricuspid valve surgery (n=945, 36.9%), isolated atrial septal defect closure (n=225, 8.8%), left atrial myxoma resection (n=54, 2.1%), and other procedures (n=73, 2.8%). The number of procedures doubled during the study period (from n=435 in 2016 to n=923 in 2019). The mean cardiopulmonary bypass time in pump assisted cases was 148.6 (63.5) min and the myocardial ischemic time was 88.7 (46.1) min. Conversion to larger thoracic incisions was required in 56 cases (2.2%). Perioperative rates of revision for bleeding, stroke, and mortality were 56 (2.2%), 6 (0.2 %), and 27 (1.1%), respectively. Median postoperative hospital length of stay was 6.6 (6.6) days. Conclusion: Robotic cardiac surgery case numbers in Europe are growing fast, including a large spectrum of procedures. Conversion rates are low and clinical outcomes are favorable, indicating safe conduct of these high-tech minimally invasive procedures.